Bookkeeping - Epstein, Lita (--For dummies., 2025)
"Bookkeeping For Dummies is a clear guide to tracking transactions, figuring out balance sheets, keeping ledgers or journals, creating financial statements, and operating accounts for businesses. This necessary resource offers relevant, up-to-date tax information and small business laws, so you'll have everything you need to conquer small business bookkeeping tasks. Looking for the latest on QuickBooks Online software, government reporting requirements, and keeping your data secure on the cloud? This new edition has you covered. Make sure your financial records and plans are accurate and complete--without taking too much time away from your business"--